Dealing with information quality in software package selection: an empirically based approach. Issue 5 (1st October 2014) - Ayala, Claudia; Franch, Xavier
Abstract : Software package selection plays a crucial role in the development of the software systems. One of its main current problems is how to deal with the vast amount of unstructured, incomplete, evolvable and widespread information that highly increases the risks of taking wrong decisions. Based on the information quality research, the authors empirically examine the meaning of information quality as perceived by software package selectors. The results were used to envisage a framework for gauging information quality in the context of diverse software package selection projects. The aim of the framework is to support software package selection decision‐making by informing selectors about the quality of the information to be used in a specific project as a risk mitigation strategy. A software tool prototype is also provided to facilitate the collection, storage, retrieval, analysis and reuse of information in a quality assurance environment. A potential scenario of use is also described as future work to be implemented in the context of an European funded project.